A Self-Powered Fast-Response Ultraviolet Detector of p–n Homojunction Assembled from Two ZnO-Based Nanowires - Wang, Yumei; Chen, Ying; Zhao, Wanqiu; Ding, Longwei; Wen, Li; Li, Haixia; Jiang, Fan; Su, Jun; Li, Luying; Liu, Nishuang; Gao, Yihua (Nano-Micro Letters, 2016)
Nowadays, fabrication of micro/nano-scale electronic devices with bottom-up approach is paid much research attention. Here, we provide a novel micro/nano-assembling method, which is accurate and efficient, especially suitable for the fabrication of micro/nano-scale electronic devices. Using this method, a self-powered ZnO/Sb-doped ZnO nanowire p–n homojunction ultraviolet detector (UVD) was fabricated, and the detailed photoelectric properties were tested. At a reverse bias of −0.1 V under UV light illumination, the photoresponse sensitivity of the UVD was 26.5 and the rise/decay time of the UVD was as short as 30 ms. The micro/nano-assembling method has wide potential applications in the fabrication of specific micro/nano-scale electronic devices.